A Study on the Usage of Learning Management Systems in Higher Education - Wulandari, Dewi Arianti; Soeprobowati, Tri Retnaningsih; Nugraheni, Dinar Mutiara K; Wandy, Wandy (Jurnal Teknologi, 2023)
This research aimed to determine the extent to which the learning management system helps in online teaching and learning activities makes learning administration and management more accessible, and makes learning activities more effective. The research used primary data from a survey from universities in West Jakarta that 69% of most respondents used a learning management system, whether they are using the existing learning management or building their own, and 44% are using Moodle application as their learning management system media. Student readiness was 69%, meaning that most were familiar with using media devices in online learning, and 92% of teaching staff, both lecturers/mentors and instructors, have experience using and evaluating online learning. Universities in West Jakarta have used learning management systems to assist the process of learning activities so that they can be used as a reference for developing online learning models.